2022
DOI: 10.1021/acsami.1c21003
|View full text |Cite
|
Sign up to set email alerts
|

A Soft Sponge Sensor for Multimodal Sensing and Distinguishing of Pressure, Strain, and Temperature

Abstract: Soft wearable sensors are essential components for applications such as motion tracking, humanmachine interface, and soft robots. However, most of the reported sensors are either specifically designed to target an individual stimulus or capable of responding to multiple stimuli (e.g., pressure and strain) but without the necessary selectivity to distinguish those stimuli. Here we report an elastomeric sponge-based sensor that can respond to and distinguish three different kinds of stimuli: pressure, strain, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…This commonly occurred phenomenon for strain sensor is due to the polymer chain disruption within the sensor materials that disturb the electron transfer along PEDOT backbone. 72 The strain also results in the loss of conductive path which causes difficult electron pass, and a crack generation led to electrical breakdown at higher strain. 73 We did run a simple resistivity measurement on 12% EG-PEDOT:PSS/PVA thin films by using finger-touching, to see its potential to be applied as pressure sensors.…”
Section: Resultsmentioning
confidence: 99%
“…This commonly occurred phenomenon for strain sensor is due to the polymer chain disruption within the sensor materials that disturb the electron transfer along PEDOT backbone. 72 The strain also results in the loss of conductive path which causes difficult electron pass, and a crack generation led to electrical breakdown at higher strain. 73 We did run a simple resistivity measurement on 12% EG-PEDOT:PSS/PVA thin films by using finger-touching, to see its potential to be applied as pressure sensors.…”
Section: Resultsmentioning
confidence: 99%
“…Benefiting from its porous structure, hydrophilic (Fig. 2j) and elasticity, the sponge provides a good solution for preparing breathable and comfortable sensors [50][51][52][53] .…”
Section: Results and Discussion Preparation And Characterization Of P...mentioning
confidence: 99%
“…In this topic, there is only a limited number of reports, as summarized in Table 4. Specifically, Lo et al 133 (Figure 4a) reported the use of soft foam to make a multimodal sensor for pressure, strain, and temperature. The soft foam was made by soaking a sugar cube in PDMS, and after curing the PDMS, removing the sugar by a simple dissolution.…”
Section: D Structural Support Approachmentioning
confidence: 99%
“…(A) Photos and optical micrographs showing the white and brown sugar cubes used as templates and the corresponding PDMS and PEDOT:PSS/PDMS sponges after each fabrication step. Reprinted with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Soft Electronics Fabrication Approachesmentioning
confidence: 99%